AFFECTIVE IMMERSION ACROSS PRINT AND SCREEN: READING MALAY ROMANCE NOVELS IN THE DIGITAL AGE - Osman, Rahmah Ahmad H.; Zulkiflee, Nurafreena Irdiena; Yaapar, Md. Salleh; Ali, Adham Hamawiya; Che Amran, Aisyah Aminah (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study investigates why Malay romance novels, particularly those written by the popular author Anjell, remain compelling to Malaysian undergraduates, and how reading medium shapes the experience of romance reading. Grounded in Reader-Response Theory (Rosenblatt, 1978), Media Ecology (McLuhan, 1964), and Affective Reading scholarship (Miall & Kuiken, 2002), the study adopts a descriptive exploratory mixed-methods design. Data were collected from undergraduates at the International Islamic University Malaysia (IIUM) through an online questionnaire (n = 20) and semi-structured interviews (n = 3). Descriptive statistics summarised survey patterns, while thematic analysis examined meaning-making, immersion, and emotional resonance across print and digital environments. Findings indicate that romance reading is sustained by affective mechanisms such as emotional conflict, relational tension, and character-based identification, with Anjell’s appeal emerging from how readers actively co-construct emotional meaning. Print reading is associated with stronger focus and deeper narrative absorption, whereas e-books are valued for accessibility, affordability, and portability, reflecting hybrid reading strategies rather than a simple print–digital divide. The study contributes to Malay popular-literature scholarship by centring real readers’ responses and offers implications for publishers and educators seeking to support reading culture in digitally saturated contexts.